Overvoltage Protection for High Frequency High Voltage Power Transformers - Diego Teruo Mendes de Souza; Bruno Valverde; José Antenor Pomilio (Eletrônica de Potência)
Transformers with high-voltage operation may have undesired behavior due to the effects of their parasitic elements. In power electronics applications, if the primary voltage has harmonics, transformer resonances may be excited, causing high primary currents and secondary voltage stress, compromising the device isolation. This behavior is quite dangerous if the transformer operates without load, what means, without damping, because in this situation, the secondary voltage peak can reach more than two times the expected (rated) value. To protect the high frequency high voltage transformer against this dangerous operation, the overvoltage problem in open load condition is carefully explored and explained in this paper, with the proposition of different protection strategies to mitigate its effect, depending on the transformer parasitic elements values. The different strategies are analytically explained and validated by experimental results, showing their criteria design and effectiveness for the protection of high frequency high voltage transformers through the analysis of a 1 kVA, 311V, 20 kHz, 42/512 ferrite core transformer, showing its dynamics working alone and with each protection strategy.